2018
DOI: 10.3906/elk-1710-27
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of PMUs via hybrid PMU-RTU communication changeover in the case of cyberattack on vulnerable power transmission lines

Abstract: A power grid strictly depends on information and communication technology. The key role of real-time measurement and information control for the reliable operation of a power grid is the responsibility of the phase measurement units (PMUs). As smart power grids encounter a variety of unauthorized malicious accesses such as cyberattacks, PMU placement is an important problem. In this study, a new algorithm was proposed to specify the minimum number of PMUs in the case of cyberattacks on their communication line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…For example, Liu and Li showed that an attacker can attack the real-time topology using the local network information of a power grid [23]. Cyberattacks are based on the information of actual meters to sabotage electrical networks, the most important of which are PMUs [24]. Therefore, reducing transient measurement information by reducing actual measurements or optimal locating processes will make the network more robust to FDI [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Liu and Li showed that an attacker can attack the real-time topology using the local network information of a power grid [23]. Cyberattacks are based on the information of actual meters to sabotage electrical networks, the most important of which are PMUs [24]. Therefore, reducing transient measurement information by reducing actual measurements or optimal locating processes will make the network more robust to FDI [24].…”
Section: Introductionmentioning
confidence: 99%
“…Cyberattacks are based on the information of actual meters to sabotage electrical networks, the most important of which are PMUs [24]. Therefore, reducing transient measurement information by reducing actual measurements or optimal locating processes will make the network more robust to FDI [24]. Isozaki et al showed how data integrity attacks in the DN can certainly affect the power quality at the consumer's side, damage power devices in DNs, and cause economic impacts on the revenue of DG owners [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation